PENGARUH DIVERSIFIKASI OPERASIONAL DAN PROFITABILITAS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN BUMN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mohamad Ali Wairooy (INVOICE : JURNAL ILMU AKUNTANSI, 2020)
This study aims to examine and analyze the effect of operational diversification and profitability on capital structure in state-owned banking companies listed on the Indonesia stock exchange. Data collection uses secondary data by using purposive sampling technique. The population in this study were all state-owned banking sector companies listed on the Indonesia stock exchange during the period 2008-2016 a total of 41 companies, while the sample taken met the criteria of 4 companies the number of observations for 9 years (2008-2016). The data obtained were analyzed using multiple linear regression analysis. The results showed that all hypotheses had a positive and significant effect based on the F test and t test. This means that both simultaneous and partial operational diversification and profitability have a positive and significant effect on the capital structure of state-owned banking companies listed on the Indonesia stock exchange.